Determination of Organizational Stress and Organizational Burnout Levels of Mid Level Managers Working in Four and Five Star Hotel Businesses - Yirik, Sevket; Ören, Deniz; Ekici, Remziye (International Review of Management and Marketing, 2015)
The present study emphasizes the concepts of stress and organizational stress which are the main concepts constituting theoretical foundation of the research; evaluates influences of stress on organization; discusses the concept of organizational burnout as well as its sub-dimensions; and analyses organizational stress and burnout levels of mid level managers working in four and five star hotels. The purpose of this study is to analyze the relationship between organizational stress and organizational burnout levels of mid level managers of four and five star hotel businesses. Survey has been conducted on 318 employees of four and five star hotels operating in Alanya, Turkey. According to the analysis of data, it has been observed that ages of mid level managers have an influence on their organizational stress and burnout levels. Genders of mid level managers are influential on their organizational stress levels while they have no influence on their burnout levels. Education levels of managers influence their organizational stress levels while they have no influence on their burnout levels. The departments of managers are influential both on organizational stress and burnout. Positions of managers influence their burnout levels while they have no influence on their organizational stress levels. Keywords: Hotel Personnel; Organizational Stress; Organizational Burnout; Tourism JEL Classifications: L83; M1